The body angle of attack in front crawl performance in young swimmers - Strzala, M.; Krezalek, P. (Human Movement, 2010)
Among factors influencing frontal (form) resistance in swimming the angle between the swimmer's body and the line of his/her horizontal movement is particularly important. The measurement of this angle called the angle of attack (?) represents indirectly active torque (?a) during swimmer's body movement. Purpose. The aim of the study was to measure the angle of attack in front crawl swimming in young swimmers at long (2000 m), medium (400 m) and short (25 m) distances and to examine the correlation between the angle and swimming speed at those distances. Basic procedures. Swimmers' angles of attack formed between the line of swimmer's movement direction (horizontal direction) and (a) the line connecting the swimmer's hips and goggles (Alpha H-G) and (b) the line connecting the swimmer's hips and shoulders (AlphaH-S) were measured. Main findings. The body angle of attack in front crawl swimming was negatively correlated with swimming speed. In the analysis of AlphaH-G (7.3± 2.74°) with swimming velocity at 2000 m the correlation was on the verge of statistical significance (-0.38, p<0.06). Conclusions. The angle of attack index in controlled front crawl swimming races at the distances of 2000, 400 and 25 m was negatively correlated with swimming speed only at 2000 m, and it was smaller in older, more experienced swimmers.